التحديات البيئية في العراق : سبل معالجة مستقاة من التجربة الألمانية (المجلة العراقية للعلوم الاقتصادية, 2018)
This study was Displays the problem of deteriorating environmental conditions experienced by Iraq and is still, as it sought to analyze a range of challenges in the environment of Iraq, for the period 2003-2010. The study used descriptive and analytical approach to address the phenomenon, as well as draw lessons from international experiences, especially the successful German experience in this area, also addressed the environmental challenges at the national and international levels. The traditional view that prevailed, and based on the separation of the environmental dimension of economic and social dimensions of development interactions has changed, especially after the establishment of the Ministry of Environment in 2003, and after approval by the Iraqi Council of Representatives on environmental laws, and on impact of Iraq to the international community, and conclusion of international agreements in the field of environment and sustainable development, as well as the emergence of civil society organizations, which have undertaken the responsibility of defending the environment in Iraq. The study concluded that in order to address the environmental challenges, and reduce their impact on the path of sustainable development, needs to be a national